Analisis Dispersi Gas Hidrogen Sulfida (H2S) dan Amonia (NH3) di Udara Ambien menggunakan AERMOD: (Studi Kasus Area Tempat Pemrosesan Akhir (TPA) Griyo Mulyo Jabon, Sidoarjo) - Putri, Imro’atul Azizah Rini Setya; Nilandita, Widya; Falasifah, Nihlatul (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
The Griyo Mulyo Jabon Landfill (TPA) in Sidoarjo has the potential to emit hydrogen sulfide (H₂S) and ammonia (NH₃) gases due to the anaerobic decomposition of organic waste. The release of these gases may contribute to ambient air quality deterioration, unpleasant odors, and reduced environmental comfort for surrounding communities. Furthermore, meteorological conditions significantly influence the transport and dispersion behavior of landfill gas emissions in the atmosphere. This study aimed to determine H₂S and NH₃ concentrations in ambient air, assess their compliance with applicable air quality standards, and evaluate the dispersion patterns of these gases around the Griyo Mulyo Jabon Landfill using atmospheric dispersion modelling. A quantitative approach was applied using the Gaussian dispersion model AERMOD. Ambient air sampling was conducted at four monitoring locations, including two points within the landfill area and two points outside the landfill boundary. Hydrogen sulfide (H₂S) concentrations were measured according to SNI 8605:2018, while ammonia (NH₃) concentrations were analyzed based on SNI 19-7117.6-2005 using the impinger method. Meteorological parameters, including wind direction, wind speed, air temperature, and humidity, were incorporated as model inputs. Model performance was evaluated using the Mean Absolute Percentage Error (MAPE) and Index of Agreement (IOA). The results showed that H₂S concentrations in the old and new landfill zones were 0.03 ppm, while NH₃ concentrations were 2.10 ppm and 2.27 ppm, respectively. The highest concentrations occurred in the active waste disposal area. The dispersion simulation demonstrated that gas movement followed the dominant east-southeast wind direction, with concentrations decreasing as the distance from the emission source increased. The low MAPE values (0.4% for H₂S and 0.3% for NH₃) indicated excellent model accuracy in representing field conditions.